Local Closure Functions in Hereditary Generalized Topological Spaces - Ramesh, R.; Prakash, Krishna; Anbumani, N. (Journal of Informatics and Mathematical Sciences, 2018)
In this paper, we introduce and study the notions of local closure functions and also we introduce the operator \(Ψ_Γ\) in hereditary generalized topological spaces.